PERSEPSI PENDAMPINGAN PERAN ANGGOTA KOPKAR TNI AD DALAM MELAKUKAN MANAJEMEN PENINGKATAN KESEJAHTERAAN DI MASA PANDEMI - Taufik Hidayat; Nuri Aslami (Transpublika Publisher, 2022)
The decline in income for Employee Cooperative (Kopkar) members, especially within the scope of the Indonesian Army (TNI), is a result of the Covid-19 pandemic's impact. As a direct consequence, it is not unavoidable for members to use cooperatives as a means for economic preservation. This study aims to gain a better understanding of the economy's happiness and prosperity and to strengthen the management function of TNI members during the Covid-19 pandemic. This research method is qualitative in nature and is primarily focused on data analysis by data reduction, data presentation, and results. The technique employed reveals that the presence of the Employee Cooperative of Indonesian Army during the Covid-19 pandemic contributed significantly in addressing the daily necessities of Indonesian military troops in the form of food and other necessities. The cooperative operates a savings and lending unit system to assist personnel of the Indonesian Army and their families with everyday necessities throughout the pandemic. Savings and loan units are monies borrowed for the following month and paid back by a monthly salary deduction for each member. Therefore, it can be concluded that the establishment of cooperatives to address the basic and daily needs of the community and members of the TNI AD in order to stabilize the business through the administration of the Employee Cooperative (Kopkar) Kodam 1/Bukit Barisan program.